UNDERGRADUATE STUDENTS’ AND LECTURERS’ PERCEPTIONS ON TEACHING STRATEGIES THAT COULD ENHANCE HIGHER ORDER THINKING SKILLS (HOTS) - Collin Jerome; Julia Lee Ai Cheng; Ting Su Hie, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The issue of higher order thinking skills (HOTS) among undergraduate students in Malaysia continues to be debated, given the lack of such skills among fresh graduates and the industry’s demand for job-ready and skillful workers. While there have been many studies examining HOTS among undergraduate students in the country, more needs to be known about the teaching strategies used during tertiary instruction that could enhance those skills. This article discusses findings from a study that investigated undergraduate students’ and lecturers’ perceptions on the teaching strategies that could enhance HOTS in the tertiary instruction context. A self-reported survey was used to gather the views of 120 undergraduate students and 20 lecturers from Universiti Malaysia Sarawak. The findings show that the types of teaching strategies that students and lecturers perceived to enhance HOTS include lectures, discussions, problem-based learning, case-based scenarios, and demonstrations. Interestingly, most lecturers used ‘enhanced’ version of lecture and discussion that incorporated a range of delivery techniques such as online learning that could enhance HOTS. The findings also show that the strategies used by the lecturers may depend on several factors such as the subject taught, the learning tasks, their own teaching approaches, as well as the link between their intention and the strategies used during instruction. It is hoped that the article will contribute to the study of HOTS, particularly the importance of considering teaching strategies that could enhance them.